Design, Development, and Validation of an Augmented Reality-Enabled Production Strategy Process - Nassereddine, Hala; Veeramani, Dharmaraj; Hanna, Awad S. (Frontiers in Built Environment, 2022)
The Production Strategy Process (PSP) is an integral part of production planning and control as it defines how production processes are structured and designed and outlines how production will be executed. PSP involves massive information transfer and communication among project participants. While BIM can improve the flow of information, the paradox of designing 3D models in 2D space remains. This paradox indicates that new visualization technologies are needed to leverage the use of information in the PSP. As Industry 4.0, the fourth industrial revolution, continues to evolve, it is imperative that construction firms seek, find, and adopt new technologies. This research employed Augmented Reality (AR) as a new user interface in the PSP. The current state of practice of PSP was investigated and current challenges are identified. The opportunities to integrate AR were defined, and an AR-enabled future state was proposed. Next, an AR-enabled PSP prototype using the Microsoft HoloLens was implemented and validated on a real-world healthcare project. Usability testing was then conducted using a one-on-one protocol to validate the prototype with 20 participants. Surveys were the deployed to qualitatively assess the impact of integrating AR into PSP. The difference between the traditional PSP and the AR-enabled PSP was tested through a series of hypotheses comparing both processes. The results demonstrate that the AR-enabled PSP offers significant benefits over the Traditional PSP: improved collaboration, reduced miscommunication, increased quality and detection of errors, enhanced decision-making, better documentation, better information access, improved information flow, increased input accuracy, and increased integration of safety considerations. Additionally, the technology, software, and hardware were also evaluated, and, on average, the findings demonstrated the potential of AR in production planning.